Poly(hydroxamic acid) Palladium Catalyst for Heck Reactions and its Application in the Synthesis of Ozagrel - Sarkar, Shaheen M.; Lutfor, M. R.; Chong, Kwok Feng; M. M., Yusoff (Elsevier, 2017)
Bio-waste corn-cob cellulose supported poly(hydroxamic acid) palladium complex was synthesized and it is characterized using some different techniques such as FTIR, FESEM, HRTEM, EDX, XPS, UV–vis, TGA and ICP-AES analyses. The cellulose supported heterogeneous palladium complex showed high stability and catalytic activity toward Mizoroki-Heck reaction of aryl/heteroaryl halides and arenediazonium tetrafluoroborate with a variety of olefins to give the corresponding coupling products in up to 97% yield. The palladium complex was also applied to the synthesis of Ozagrel a thromboxane A2-synthetase inhibitor with excellent yield. The complex was separated from the reaction mixture by simple filtration and repeatedly used up to seven times without significant loss of its catalytic performance.